Trascendencia del liderazgo y organización comunitaria en el desarrollo local de la parroquia la Victoria, cantón Santa Rosa - Matamoros Gaona, Carla Gisselle; Reyes Huanga, Andrea Paulette (Machala: Universidad Técnica de Machala, 2021)
This research focuses on the study of the significance of leadership and community organization in the local development of La Victoria parish, canton of Santa Rosa. The main problem of the community, has to do with the administration of the Parish GAD La Victoria, whose authorities do not maintain horizontal communication with the inhabitants, which is why the participation of the inhabitants is not active, there is weak administrative and leadership management which causes problems in progress for the place. Another difficulty is that the inhabitants are not aware of the roles of the members of the Parish GAD, noted in COOTAD art. 307 literals a-h, this results in the absence of evaluation of the programmes or projects they implement, which results in the needs being neglected, and it is also found that there is no planning or programming of activities that promote community participation which generates disinterest and individuality in the processes. The study of the context arises from the importance of knowing the direct reality, depending on proposing solution alternatives that contribute to the development of the place and in turn achieve union between the inhabitants. The place of study is located in the province of El Oro, canton Santa Rosa, parish La Victoria, its boundaries are to the north, with the parish Buenavista of the canton Pasaje; to the south, rural parish Cerro azul of the canton Atahualpa, to the East, parish Pasaje and Buenavista of the canton Pasaje; to the west, urban parish Santa Rosa, parish of Machala and Ayapamba parish of the canton Atahualpa. The central question guiding the research is. What is the significance of leadership and community organization in the local development of the parish La Victoria of the canton of Santa Rosa, has the general objective been raised: To determine the significance of leadership and community organization in the local development of the parish La Victoria. The epistemological approach is hypothetical-deductive or logical-deductive, the type of research is descriptive and explanatory, the methodology used corresponds to the quantitative approach, methods such as, observation, analysis and explanation have been applied; among the instruments of inquiry is the survey and observation. The results of the investigation show that parish dwellers lack information, which means that the authorities do not generate alternatives for solving the problems of the place; the inhabitants are not aware of the decisions they make for the benefit of the parish in meetings convened by the Municipal GAD. Weak community involvement in the development of community projects; the absence of proposals for the development of the Parish. Based on the results obtained, a proposal for intervention is proposed with the theme Community participation and local development giving two results: Workshop aimed at identifying the profile of the participating inhabitants, which allows to know the skills and skills, and thus know what are the best channels of communication for them, workshop aimed at community participation and local development of the Parish to contribute to improving its quality of life.
La presente investigación se orienta al estudio de la trascendencia del liderazgo y la organización comunitaria en el desarrollo local de la parroquia La Victoria, cantón Santa Rosa. El problema principal de la comunidad, tiene que ver con la administración del GAD Parroquial La Victoria, cuyas autoridades no mantienen una comunicación horizontal con los pobladores, razón por la cual la participación de los moradores no es activa, hay una débil gestión administrativa y de liderazgo lo que provoca problemas en los avances para el lugar. Otra dificultad es que los habitantes no tienen conocimiento de las funciones que desempeñan los miembros del GAD Parroquial, señaladas en el COOTAD art. 307 literales a-h, lo que provoca ausencia de evaluación de los programas o proyectos que ejecutan, lo que da como resultado que las necesidades sean desatendidas, además se constata que no existe una planificación ni programación de las actividades que promueven la participación comunitaria lo que genera desinterés e individualidad en los procesos. El estudio del contexto nace de la importancia por conocer la realidad directa, en función de proponer alternativas de solución que contribuyan al desarrollo del lugar y a su vez lograr la unión entre los moradores. El lugar de estudio se encuentra ubicado en la provincia de El Oro, cantón Santa Rosa, parroquia La Victoria, sus límites son al norte, con la parroquia Buenavista del cantón Pasaje, al sur, parroquia rural Cerro azul del cantón Atahualpa, al Este, parroquia Pasaje y Buenavista del cantón Pasaje; al oeste, parroquia urbana Santa Rosa, parroquia de Machala y parroquia Ayapamba del cantón Atahualpa. La pregunta central que orienta la investigación es Qué trascendencia tiene el liderazgo y la organización comunitaria en el desarrollo local de la parroquia La Victoria del cantón Santa Rosa, se ha planteado el objetivo general. Determinar la trascendencia del liderazgo y organización comunitaria en el desarrollo local de la parroquia La Victoria. El enfoque epistemológico es hipotético-deductivo o lógico-deductivo, el tipo de investigación es descriptiva y explicativa, la metodología utilizada corresponde al enfoque cuantitativo; se ha aplicado métodos como, la observación, análisis y explicación, entre los instrumentos de averiguación está la encuesta y la observación. Los resultados de la investigación se evidencian que los moradores de la parroquia carecen de información lo cual provoca que las autoridades no generen alternativas de solución ante los problemas que tiene el lugar; los habitantes no tienen conocimiento de las decisiones que toman en beneficio a la parroquia en reuniones convocadas por el GAD Municipal. La débil participación de la comunidad en la elaboración de proyectos comunitarios, la inexistencia de propuestas para el desarrollo de la Parroquia. En base a los resultados obtenidos, se plantea una propuesta de intervención con la temática Participación comunitaria y desarrollo local dando dos resultados, Taller dirigido a identificar el perfil de los moradores participantes, que permita conocer las habilidades y destrezas, y así saber cuáles son los mejores canales de comunicación para ellos, taller dirigido a la participación comunitaria y desarrollo local de la Parroquia para contribuir a mejorar su calidad de vida.
Keywords: PARTICIPACION COMUNITARIA; DESARROLLO LOCAL; LIDERAZGO